Cryptolepine Targets TOP2A and Inhibits Tumor Cell Proliferation in Breast Cancer Cells - An In vitro and In silico Study - Mehraj, Umar; Qayoom, Hina; Shafi, Shazia; Farhana, Pzd; Asdaq, Syed Mohammed Basheeruddin; Mir, Manzoor Ahmad (Anti-cancer agents in medicinal chemistry, 2022)
DNA Topoisomerase II Alpha (TOP2A), a protein-coding gene, is central to the replication process and has been found deregulated in several malignancies, including breast cancer. Several therapeutic regimens have been developed and approved for targeting TOP2A and have prolonged the survival of cancer patients. However, due to the inherent nature of the tumor cell to evolve, the earlier positive response turns into a refractory chemoresistance in breast cancer patients. The study's main objective was to analyze the expression pattern and prognostic significance of TOP2A in breast cancer patients and screen new therapeutic molecules targeting TOP2A. We utilized an integrated bioinformatic approach to analyze the expression pattern, genetic alteration, immune association, and prognostic significance of TOP2A in breast cancer (BC) and screened natural compounds targeting TOP2A, and performed an in silico and an in vitro analysis. Our study showed that TOP2A is highly overexpressed in breast cancer tissues and overexpression of TOP2A correlates with worse overall survival (OS) and relapse-free survival (RFS). Moreover, TOP2A showed a high association with tumor stroma, particularly with myeloid-derived suppressor cells. Also, in silico and in vitro analysis revealed cryptolepine as a promising natural compound targeting TOP2A. Cumulatively, this study signifies that TOP2A promotes breast cancer progression, and targeting TOP2A in combination with other therapeutic agents will significantly enhance the response of BC patients to therapy and reduce the development of chemoresistance.